RELEVANSI PENGECUALIAN PRAKTIK MONOPOLI TERHADAP PERUSAHAAN BUMN DALAM MERGER TIGA BANK SYARIAH BUMN - Chandra Manungsa Alit; Yeti Sumiyati (Dialogia Iuridica, 2021)
This study examines the following issues: first, whether the merger of 3 state-owned sharia banks is included in the criteria for monopolistic practice as an activity prohibited in the Law on monopolistic practices and unfair business competition. Second, what is the relevance of the provisions of the exclusion of monopolistic practices on BUMN in the Law on monopolistic practices and unfair business competition to the merger of 3 BUMN sharia banks. This study uses a normative juridical method. The results showed that the merger or merger of 3 state-owned sharia banks could potentially lead to monopolistic practices and unfair business competition as prohibited by Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition.